2018
DOI: 10.5670/oceanog.2018.224
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Benthic Macrofaunal Populations, Seasonal Sea Ice Persistence, and Bottom Water Temperatures in the Bering Strait Region

Abstract: Recent declines in sea ice extent and warming seawater temperatures in the Arctic have the potential to impact regional and pan-Arctic marine ecosystems. To investigate marine biological response to these key drivers and other environmental factors, we undertook a robust trend analysis of benthic macrofaunal populations and environmental drivers in the Bering Strait region. Our focus was on the waters of the northern Bering and southern Chukchi Seas, which are shallow (<100 m) and seasonally productive, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 52 publications
1
73
0
Order By: Relevance
“…In the Pacific Arctic food webs, even small changes in the lower trophic levels would have an influence on the distribution and abundance of higher trophic levels as a consequence of the short and efficient energy-transfer pathways (Grebmeier et al, 2010), and thus the bottom-up control on higher trophic levels is crucial (Schonberg et al, 2014). This study revealed an increased occurrence of fall blooms, which has the potential to explain recent variations in benthic macrofaunal biomass at the DBO sites (Grebmeier et al, 2018;Waga et al, 2019). Consequently, our findings contribute to facilitate an holistic understanding of ocean dynamics and complex trophic linkages from primary production to higher trophic levels, and improve our understanding of processes causing variations within marine ecosystems, as might occur in the Pacific Arctic.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In the Pacific Arctic food webs, even small changes in the lower trophic levels would have an influence on the distribution and abundance of higher trophic levels as a consequence of the short and efficient energy-transfer pathways (Grebmeier et al, 2010), and thus the bottom-up control on higher trophic levels is crucial (Schonberg et al, 2014). This study revealed an increased occurrence of fall blooms, which has the potential to explain recent variations in benthic macrofaunal biomass at the DBO sites (Grebmeier et al, 2018;Waga et al, 2019). Consequently, our findings contribute to facilitate an holistic understanding of ocean dynamics and complex trophic linkages from primary production to higher trophic levels, and improve our understanding of processes causing variations within marine ecosystems, as might occur in the Pacific Arctic.…”
Section: Discussionmentioning
confidence: 66%
“…As phytoplankton size structure during the post-bloom period strongly determines the amount of the flux of organic carbon into the sediment (Waga et al, 2019), interannual variations in phytoplankton size structure during the post-bloom period could influence not only the occurrence of a fall-bloom but also increased activity of higher trophic levels in the food web. Indeed, several studies have reported decreasing and increasing trends in benthic macrofaunal biomass at DBO1 and DBO3, respectively, while that of DBO2 showed an insignificant trend at DBO2 (Grebmeier et al, 2018;Waga et al, 2019). Fall blooms are observed to occur more frequently in the Arctic Ocean during the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that with future warming, the Chukchi Sea may bloom prior to an ice‐free Bering Sea. In addition, the absence of sea ice and the associated flux of ice algae to the bottom likely had a profound impact on the relatively high, but varying, benthic community biomass found over the northern shelf (Grebmeier et al, ; Grebmeier et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Trends in sea ice extent and duration are variable from year-to-year and throughout the Arctic [31]. Across the Pacific Arctic region (Bering, Chukchi and Beaufort Seas), sea ice break-up is occurring earlier and forming later, leading to younger and thinner sea ice annually with persistence declining by 9 to 30 days per decade over the satellite record [15,[31][32][33]. Two record low maximum winter extent periods for the Bering Sea occurred in 2018 and 2019, along with a record low summer minimum extent for the Chukchi Sea in 2019 [33][34][35].…”
Section: Introductionmentioning
confidence: 99%